Герб. Флаг. Гимн СССР - Гнидаш Владимир Семенович (Библиотечка политинформатора "Вопрос - ответ", 1985)
Экземпляры: КХ (20150727) / Инвентарный номер: 0271047 / Цена: 0.15 / Сис.шифр: 34С / Авт.знак: Г 56 / ГРНТИ: 10 / ББК: 67